Joy is a distinct positive emotion: Assessment of joy and relationship to gratitude and well-being. Issue 5 (3rd September 2018) - Watkins, Philip C.; Emmons, Robert A.; Greaves, Madeline R.; Bell, Joshua
Abstract: In three studies we investigated joy and its relationship to subjective well-being (SWB). We developed measures of joy based on recent conceptualizations of joy in the humanities and social sciences. In Studies 1 and 2 we developed reliable measures of state and trait joy. In Study 3 we used a two-month prospective design to investigate the relationship of joy to gratitude and SWB. We found that dispositional gratitude predicted increases in state joy over time. We also found that trait joy predicted increases in state gratitude, providing evidence for an intriguing upward spiral between joy and gratitude. Finally, we found that trait joy was associated with increases in SWB over time. Factor analyses indicated that joy loaded separately from other positive emotions. We conclude that joy is a discrete positive emotion, it can be measured reliably with self-report instruments, and that it may be an important component of well-being.